PENGARUH STRES KERJA TERHADAP KINERJA KARYAWAN OUTSOURCING BAGIAN FEED PT. X - Nurul Oktavia Puspita Sari; Ida Wahyuni; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
One of the efforts of an organization or company in achieving its goal was by having a good performance. There were several factors that affect the performance of employees, one of which was the job stress. The purpose of this research was to analyze the effect of job stress on performance of outsourcing employee on feed division in PT. X. This was an explanatory research with cross sectional method. The number of samples in this study were 57 respondents. The data analysis was using logistic regression test to determine whether the job stress affects the employees performance. The results showed that 71,9% of respondents were having high level of job stres, and 70,2% of respondents were having low level of performance. Crosstab bivariat analysis showed that 65,8% respondent with high level of job stress were having low performance. Logistic regression test with p value Wald test (Sig) 0,261 ≥ 0,05 meant that there were no significant effect of job stress on employees performance. Therefore it can be concluded that there were no significant effect of job stress on employees performance. It was recommended for the company to make posters that contain job descriptions, organize recreational activities or outbound, give reward and provide a suggestion box.